Online Intergroup Polarization Across Political Fault Lines: An Integrative Review - Bliuc, Ana-Maria; Bouguettaya, Ayoub; Felise, Kallam D. (Frontiers in Psychology, 2021)
We revisit the construct of political polarisation and current distinctions between issue-driven and affective polarisation. Based on our review of recent research on polarisation from psychology, political science, and communication, we propose to treat polarisation as a process that integrates the concepts of social identification (collective self-definition) with ideologically opposed camps - that is, psychological groups based on support or opposition to specific socio-political issues and policies (related to issue-driven polarisation), and that of ideological and psychological distancing between groups (related to affective polarisation). Furthermore, we discuss the foundations of polarising groups - and more specifically, the role of conflicting collective narratives about social reality in providing an initial platform for polarisation in a technologically networked world. In particular, we highlight the importance of online media in facilitating and enhancing polarisation between ideologically opposed camps. As a theoretical contribution, the review provides a more functional conceptualisation of polarisation that can explain how polarisation may occur across partisan fault lines and in domains outside of politics. We conclude with a discussion of new pathways to the study of polarisation which this integrative conceptualisation opens.